2006
DOI: 10.1021/bc060078q
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Linked Fluorescent Molecular Beacons with Enhanced Cell Permeability

Abstract: We appended pyrene units covalently onto adenosine (forming A(P) units) and then incorporated them into oligonucleotides such that they were positioned in complementary locations in opposite strands in the middle positions of hairpin stems. System 1 (A(P)A(P)) behaves as an effective molecular beacon (MB) that changes color from green to blue upon duplex formation. In addition, we attached a cholesterol unit to a free terminus of one of these hairpins; this approach enhanced the cellular delivery of the modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…1) (16), however, demonstration of their formation in living cells remains elusive. To investigate whether TERRA RNA G-quadruplexes exist in living cells, we employed a light-switching pyrene probe that has been designed to employ the capability of pyrene to form fluorescent excited-state dimers (excimers) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The advantage of the distance dependence of excimer formation with pyrene can be used as a unique excimer signaling device for detecting G-quadruplex structure ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) (16), however, demonstration of their formation in living cells remains elusive. To investigate whether TERRA RNA G-quadruplexes exist in living cells, we employed a light-switching pyrene probe that has been designed to employ the capability of pyrene to form fluorescent excited-state dimers (excimers) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The advantage of the distance dependence of excimer formation with pyrene can be used as a unique excimer signaling device for detecting G-quadruplex structure ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To this aim, lipid moieties have been coupled to molecules to be delivered inside the cells. For example, a cholesterol unit has been attached to a free terminus of an oligonucleotide hairpin, thus enhancing its cellular delivery in comparison to conventional transfection methods [61]. In another study, cholesterol-derivatized oligonucleotides also showed a rapid binding and cytosolic partition in cells [62].…”
Section: Cpps and Cell Entrymentioning
confidence: 99%
“…The practical utility of the free ends in EMS MBs of Figure 8.19c has been demonstrated by attaching a cholesterol moiety at the 5 -end of the ODN. The cellular permeability of the cholesterol-appended ODN was enhanced significantly as compared to that of free ODN [122]. Some fluorophores form nonradiative dimers when they are in close proximity.…”
Section: Quencher-free Molecular Beaconmentioning
confidence: 97%